Does social vulnerability for caries predict caries status of children in sub-urban Nigeria? - Morenike Oluwatoyin Folayan; Olujide Olusesan Arije (Universidade Estadual de Campinas, 2016)
It is important to identify groups of people vulnerable to a disease condition. Aim: To determine the association between social vulnerability to caries and caries status of children in Ile-Ife, Nigeria. Methods: A composite vulnerability index for caries was developed using data generated for 992 children. Wilks' Lambda test to verify relationship between vulnerability and its variables. Logistic regression analysis was conducted to determine if the social vulnerability for caries index was a good predictor for caries status. Results: The social vulnerability to caries index could not predict caries status. The study found that sex, age and number of siblings were the significant predictors of caries status in the study population. Females (AOR: 1.63; 95%CI: 1.08 - 2.46; p=0.02) and children with more than two siblings had higher odds of having caries (AOR: 2.61; 95%CI: 1.61 - 4.24; p<0.001) while children below 5 years had lower odds of having caries (AOR: 0.62; 95%CI: 0.39 - 1.00; p=0.05) Conclusions: The social vulnerability index for caries could not predict the caries status of children in the study population. Sensitive tools to identify children with caries in the study population should be developed.